2021
DOI: 10.21203/rs.3.rs-138545/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Galectin-3 In Septic Acute Kidney Injury: A Translational Study

Abstract: Background Galectin-3 (Gal-3) is a pleiotropic glycan-binding protein shown to be involved in sepsis and acute kidney injury (AKI). However, its role has never been elucidated in sepsis-associated AKI (S-AKI). We aimed to explore Gal-3’s role and its potential utility as a therapeutic target in S-AKI. MethodsIn 57 patients admitted to the intensive care unit (ICU) with sepsis, serum Gal-3 was examined as a predictor of ICU mortality and AKI. In a rat model of S-AKI induced by cecal ligation and puncture (CLP)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In vitro studies investigating galectin-3 have demonstrated that the absence of galectin-3 may improve fibrotic response in the kidneys, liver, and lungs [15,16]. Previous studies have also reported increased levels of galectin-3 in diseases progressing with fibrosis, such as cirrhosis and idiopathic pulmonary fibrosis [13][14][15][16][17]. A previous study reported that galectin-3 levels were elevated in sarcoidosis patients with cardiac involvement when compared to the controls [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies investigating galectin-3 have demonstrated that the absence of galectin-3 may improve fibrotic response in the kidneys, liver, and lungs [15,16]. Previous studies have also reported increased levels of galectin-3 in diseases progressing with fibrosis, such as cirrhosis and idiopathic pulmonary fibrosis [13][14][15][16][17]. A previous study reported that galectin-3 levels were elevated in sarcoidosis patients with cardiac involvement when compared to the controls [18].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular galectin-3 mediates inflammation and leukocyte adhesion and plays roles in the retrieval and activation of neutrophils (NEUs) [11] and also has a crucial role in the stimulation of inflammation in a wide range of acute and chronic events, particularly neurologic degeneration, autoimmune disorders, atherosclerosis and heart failure, and response to infections or diseases of the lungs, kidney, and liver [12]. A recent study by Sun et al [13] showed a relationship between galectin-3 level and prognosis of acute kidney injury. These observations suggest that galectin-3 may result in fibrosis in several systems.…”
Section: Introductionmentioning
confidence: 99%